Assistance In The Implementation of Sustainable Professional Development (PKB) For Elementary School Teachers In Malalak District, Agam Regency - Irsyad Irsyad; Anisah Anisah; Yahya Yahya; Tia Ayu Ningrum (Universitas Negeri Padang, 2022)
Improving the quality and relevance of education is influenced by several factors. One of them that affects is the quality of the learning process carried out by teachers in the classroom and or at school.. Therefore, a teacher who has high qualifications, competence, and dedication is needed in carrying out his professional duties. However, there are some teachers in Malalak District, Agam Regency who have not tried to develop their profession, and do not even know what PKB is. Observing these findings, lecturers in the Education Administration Department of FIP UNP who are members of the service team provide assistance to solve these various problems. In addition, also accompanying the teacher to conduct Classroom Action Research (CAR). Therefore, it is deemed necessary to assist the service team from the Department of Educational Administration FIP UNP carried out through workshops, focus group discussions (FGD), improvement of classroom learning, and preparation of learning improvement reports in the form of CAR. This PKM will later produce a product for each participant, namely a learning design, proposal, instrument and CAR report. and will also be published in the mass media and will be uploaded on Youtube. Keywords: Continuous Professional Development, Learning, Classroom action research